Pemetaan Distribusi Luasan Mangrove Menggunakan Metode Maximum Likelihood - Farkhatus Solikhah; La Ode Alam Minsaris; Ishak Ariawan (Jurnal Penelitian Pendidikan Geografi, 2024)
The coast of Jadimulya Village is used by the community for fish and shrimp ponds which results in abrasion due to the absence of a mangrove ecosystem to buffer abrasion. This research was conducted to determine the condition of the mangroves in Jadimulya Village over the last 5 years using remote sensing and a Geographic Information System (GIS) with the maximum likelihood classification method, so that information is obtained that can be used as reference material for research related to the field of mapping, conservation, and development of mangrove ecosystems in Jadimulya Village. The data processed for mapping in this research used Landsat 8 OLI imagery for the last five years (2018, 2019, 2020, 2021, and 2022). The research results show that the area of ​​mangroves in Jadimulya Village in 2018 was 2.85 ha, in 2019 it was 4.45 ha, in 2020 it will be 4.17 ha, in 2021 it will be 4.42 ha, and in 2022 it will be 5.3 ha. The Producer Accuracy (PA) and User Accuracy (UA) values ​​for mangrove classification are 83%, and the overall accuracy or Overall Accuracy (OA) for image classification is 85% with a kappa coefficient of 0.81.